MITIGATING CONFLICTS IN SOCIETY WITH AN UNDERSTANDING OF CIVIC EDUCATION - Muhamad Subkhan; Nono Yatno; Sri Rahayu Pudjiastuti; Pat Kurniati; Sri Rumiati (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
Conflict and conflict resolution in each individual is different, but the picture that must be understood is that it is different is beautiful. Actually life is an orchestra group where each player holds a different musical instrument, and each player plays his or her own role. From each of these differences will produce a beautiful harmony. Also when observing carefully how beautiful a rainbow is with all its differences, because with all the differences everything will look beautiful. A difference must be managed wisely, because difference is a necessity. The difference is beautiful, the difference is a pleasure, an extraordinary gift from Allah SWT. We can enjoy life because of a difference. Conflict in life together can be said to be something common, but conflicts that can endanger or threaten the integrity of life together cannot be ignored and ignored. Humans are social creatures, they can live, develop and play a role when dealing with and cooperating with other humans. Basically, the purpose of citizenship education is that citizenship is to be good citizens, namely citizens who have intelligence (civics intelligence), both intellectual, emotional, social, and spiritual, have a sense of pride and responsibility. (civics responsibility) and being able to participate in community life. With the aim of citizenship education, understanding citizenship is able to reduce conflict.